Rational design of new NO and redox sensitivity into connexin26 hemichannels - Louise Meigh (Open Biology, 2015)
CO2 directly opens hemichannels of connexin26 (Cx26) by carbamylating K125, thereby allowing salt bridge formation with R104 of the neighbouring subunit in the connexin hexamer. The formation of the inter-subunit carbamate bridges within the hexameric hemichannel traps it in the open state. Here, we use insights derived from this model to test whether the range of agonists capable of opening Cx26 can be extended by promoting the formation of analogous inter-subunit bridges via different mechanisms. The mutation K125C gives potential for nitrosylation on Cys125 and formation of an SNO bridge to R104 of the neighbouring subunit. Unlike wild-type Cx26 hemichannels, which are insensitive to NO and NO2−, hemichannels comprising Cx26K125C can be opened by NO2− and NO donors. However, NO2− was unable to modulate the doubly mutated (K125C, R104A) hemichannels, indicating that an inter-subunit bridge between C125 and R104 is required for the opening action of NO2−. In a further test, we introduced two mutations into Cx26, K125C and R104C, to allow disulfide bridge formation across the inter-subunit boundary. These doubly mutated hemichannels open in response to changes in intracellular redox potential.